Curcumin and whey protein concentrate binding: Thermodynamic and structural approach. (May 2023) - Racz, Csaba-Pal; Racz, Levente Zsolt; Floare, Calin Gabriel; Tomoaia, Gheorghe; Horovitz, Ossi; Riga, Sorin; Kacso, Irina; Borodi, Gheorghe; Sarkozi, Melinda; Mocanu, Aurora; Roman, Cecilia; Tomoaia-Cotisel, Maria
Abstract: The molecular interaction between curcumin (CCM), and whey protein concentrate (WPC), was studied by using fluorescence measurements. The binding number (n), binding constant (KS ) and thermodynamic parameters (ΔG 0, ΔH 0 and ΔS 0 ) were determined at different temperatures and various pH values. Thermodynamic approach revealed the highest stability of the 1CCM-1WPC complex in acidic medium (e.g., stomach fluid of pH 1.5), decreasing at alkaline pH (e.g., small intestine fluid of pH 7.4 to 8.0). The CCM-WPC complex as spray-dried powder was further investigated by XRD, FTIR and AFM imaging. X-ray powder diffractions show that due to the chemical interaction between CCM and WPC a new amorphous compound is formed. FTIR spectra give strong evidence for the interaction of CCM with WPC and the formation of this CCM-WPC complex. AFM images revealed the nanostructure of CCM, WPC, and of the CCM-WPC complex. Docking studies revealed hydrophobic interactions between CCM and WPC, in agreement with entropic driven formation of this 1CCM-1WPC complex leading to a better understanding of binding mechanism between these components. Therefore, this work confirmed that the WPC is a promising carrier for CCM. Lastly, the development of the 35CCM-1WPC complex, characterized by XRD, FTIR and AFM, is potentially leading to natural and safe functional foods through incorporation, distribution and high stability of these bioactive compounds jointly enhancing their biological effects for human health benefits. Graphical abstract: Image 1 Highlights: CCM and WPC complexes were synthesized by co-precipitation and spray drying. XRD, FTIR and molecular docking simulation confirmed the complexation. The thermodynamics of the complexation process at different pHs was elucidated.